Rancang Bangun Simulasi Rangkaian Foward Reverse Motor 3 Fasa - Fitroh Anugrah Kusuma Yudha; Ikhsan Fakhri Fadullah; Aditya Kurniawan (SIBER PRESS Universitas SIBERMU, 2024)
Forward reverse systems are widely used in industry, especially in industries that use drive systems during the production process. It is applied to a 3-phase electric motor, a device that serves to drive a machine. Most industries depend on electricity, an invention of the modern century. The three-phase motor system uses electrical devices to produce mechanical energy. The purpose of this study is to determine the results of the feasibility test of a three-phase motor system with a forward-reverse circuit and to achieve the goal of developing a forward-reverse control system using a three-phase motor. To collect data, descriptive techniques were used to describe the entire research flow, starting from analysing the needs of tools and materials, designing the control system, making the control system, testing, and test results. The results showed that making a system using a 3-phase induction motor that is often used in various industries in production needs can make the distribution of AC current power in the system easier. The realisation of this 3-phase motor is also able to control electricity well. Since this part is quite efficient, a 3-phase motor is used. using a mains voltage source. The tools used include a set of screwdrivers, a digital multimeter, and cable stripping and cutting pliers. There are several buttons, where voltage is supplied to the magnetic contractor forward if the forward button is pressed. If the reverse button is pressed, voltage is applied to the reverse magnetic contractor, and the motor will move in the opposite direction if it is operating.